CLASSIFICATION OF RISKS IN INVESTMENT AND CONSTRUCTION ACTIVITIES - M. Gabrielyan; O. Tretyakov (Вестник университета)
In thе article investigates the classification of risks, which is one of the most effective ways of risk management of construction companies. The aim of this publication is a compilation and systematization of some existing approaches to risk classification of investment and construction companies.